OFFLINE GAMIFIED ANKI FOR EFL VOCABULARY LEARNING: IMPLEMENTATION, BENEFITS, AND CHALLENGES - Moh. Rifki; Nina Khayatul Virdyna (ENGLISH, 2026)
This study investigates offline gamified Anki for EFL vocabulary learning at Banyuanyar English Center (BEC), a pesantren-based context with restricted internet access and limited device availability. To the authors’ knowledge, no published empirical research has specifically examined offline gamified Anki in comparable limited-access EFL settings. Using a qualitative descriptive approach with thematic analysis, the study examines how offline gamified Anki was implemented, what benefits it offered, and what challenges influenced learning quality. The study contributes context-sensitive insights to technology-supported vocabulary learning and offers practical implications for teachers, students, and institutions in limited-access EFL settings to implement offline gamified Anki routines while maintaining learning quality. Findings show that the program operated as a structured routine through scheduled sessions, shared-device turn-taking, and consistent procedures. Benefits included stronger learning sustainability through routine-building, increased engagement supported by visible progress, and improved vocabulary learning through repeated review, active recall, pronunciation cues, and contextual examples. Challenges included limited devices that encouraged rushing, difficulties maintaining accurate self-rating during review, competitive pressure associated with leaderboard visibility, and environmental noise that reduced the usefulness of audio support. Overall, offline gamified Anki appears feasible in limited-access contexts, but effectiveness depends on careful routine management, fair access to practice, and classroom guidance that prioritises learning quality over speed or scores.